2020
DOI: 10.1155/2020/2630905
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Contraceptives Use among Women Aged (15–49 years) with Induced Abortion History in Ghana

Abstract: Background. The incidence of abortion in Ghana ranges from 27 per 1000 to 61 per 1000 women, causing gynecological complications and maternal mortality. The use of modern contraceptives and its associated factors among women aged 15–49 years have been documented. However, utilization of modern contraceptives specifically among women with induced abortion history is underreported. This study therefore aimed at determining the proportion and identifying predictors of contraceptives use in this underreported popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(35 reference statements)
2
1
0
Order By: Relevance
“…While about one-fifth of our participants were teenagers, we found that almost half of the participants were younger than 25 years. This age pattern is consistent with reports from other studies that showed that women aged 20-29 years have the highest induced abortion prevalence in most countries [ 22 ]. However, Benson et al .…”
Section: Discussionsupporting
confidence: 92%
“…While about one-fifth of our participants were teenagers, we found that almost half of the participants were younger than 25 years. This age pattern is consistent with reports from other studies that showed that women aged 20-29 years have the highest induced abortion prevalence in most countries [ 22 ]. However, Benson et al .…”
Section: Discussionsupporting
confidence: 92%
“…Closely followed by the women aged 19–25 years (38.22%). This finding supports studies that women aged 20–29 years have the highest proportion of abortions in most countries [ 18 ]. It is worthy of note that teenagers younger than 19 years constituted about 10% of the abortion seekers among our cohort.…”
Section: Discussionsupporting
confidence: 92%
“…The abortion law, which was passed in 1985, states that an abortion performed by a professional medical practitioner is legal if the pregnancy is induced by rape, incest, or defilement of a "female idiot"; if continuing the pregnancy will endanger the woman's life or her physical or mental health; or if there is a significant risk that the child will suffer from a severe physical abnormality or disease. Despite the relatively liberal nature of the law in Ghana, unsafe abortions remain a major social and public health issue in the country [27][28][29][30]. According to available data, only 12% of abortions in Ghana are conducted under the guidance of a qualified medical practitioner, with the remaining 88% occurring in unsafe conditions [31].…”
Section: Introductionmentioning
confidence: 99%